Populations at Risk of Disaster : A Resettlement Guide - Correa, Elena; Ramirez, Fernando; Sanahuja, Haris (World Bank, Washington, DC, 2017)
This book is designed for governments that make decisions on the application of preventive resettlement programs as disaster risk reduction measures, as well as for institutions and professionals in charge of preparing and implementing these programs, civil society organizations participating in resettlement and risk reduction processes, and at-risk communities. The basic premises of the guide are that resettlement as a preventive measure should be incorporated in comprehensive risk reduction strategies in order to be effective; and that resettlement's objective is to protect the lives and assets of persons at risk and to improve or at least restore their living conditions. The guide has two parts. The first consists of two chapters. The first of these looks at disasters occurring worldwide and their impacts, and discusses strategic frameworks for disaster risk reduction. The second chapter analyzes resettlement as a preventive measure in the context of comprehensive risk management policy. It examines the relevance of resettlement according to the type of natural hazards and to their characteristics, as well as the savings achieved by promoting this type of resettlement rather than handling a disaster generated emergency and recovering from it. In this chapter, preventive resettlement is to be included in the public policy sphere, since it is based on recognition of the rights and responsibilities of public, private, and civil society stakeholders, and is to be guided by principles of effectiveness, equity, and general public well-being.